Pengaruh Jumlah Kehadiran Rapat Dan Usia Direktur Terhadap Csr Perusahaan Jasa Non Keuangan Di Indonesia - Priem Trisna Sulistyo; Saarce Elyse Hatane (Business Accounting Review, 2020)
This study aims to provide empirical evidence regarding the effect of board age, board meeting attendance on ESG disclosure. The control variables used are sales growth and liquidity ratio. The liquidity ratio value is calculated based on the current ratio.The sample in this study was determined based on a purposive sampling method of 27 non-financial service sector companies in the observation period of 2011 to 2016. The data analysis method used in the study was multiple regression and processed using the Gretl application. From the results of the study note that there are no major variables that affect ESG disclosure, and instead the sales growth control variable was found to have a positive influence on ESG disclosure